2022
DOI: 10.1161/circresaha.121.319994
|View full text |Cite
|
Sign up to set email alerts
|

Immune Pathways in Etiology, Acute Phase, and Chronic Sequelae of Ischemic Stroke

Abstract: Inflammation and immune mechanisms are crucially involved in the pathophysiology of the development, acute damage cascades, and chronic course after ischemic stroke. Atherosclerosis is an inflammatory disease, and, in addition to classical risk factors, maladaptive immune mechanisms lead to an increased risk of stroke. Accordingly, individuals with signs of inflammation or corresponding biomarkers have an increased risk of stroke. Anti-inflammatory drugs, such as IL (interleukin)-1β blockers, methotrexate, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 218 publications
2
101
0
3
Order By: Relevance
“…We speculated that DEGs may influence the occurrence and progression of IS through these potential pathways. Furthermore, GSEA and GSVA results showed that IS was influenced by the inflammation and immune regulation pathway, which is consistent with the current theory that inflammation and immune responses play key roles in the regulatory network of IS (Endres et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…We speculated that DEGs may influence the occurrence and progression of IS through these potential pathways. Furthermore, GSEA and GSVA results showed that IS was influenced by the inflammation and immune regulation pathway, which is consistent with the current theory that inflammation and immune responses play key roles in the regulatory network of IS (Endres et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…The data, however, showed here that there was no association between SV and PSD status, but lower SA was significantly associated with PSD status in the presence of CRP rs2794520 C/T genotype and rs1205 C/T genotype. The mechanisms underlying the associations may be that owing to the contribution of CRP polymorphism and CRP levels to immuno-inflammatory process ( 32 , 37 ), patients with the C/T genotypes of rs2794520 and rs1205 may be in a more active inflammatory state so that immune cells and cytokines produced abundantly in the spleen, in response to brain vascular damage, were released into the bloodstream and migrated to the site of brain insult ( 17 , 20 ), aggravating secondary brain inflammatory response which influences serotonin metabolism and causes noradrenergic system and HPA axis imbalance, may culminate in PSD ( 6 , 42 ). There in addition were evidence from animal studies for the involvement of pro- and anti-inflammatory cytokines produced by splenic cells in the formation of depression like behavior ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…After severe cellular damage occurs in the ischemic region, damaged cells release several DAMPs, including adenosine, heat shock proteins, high mobility group box 1 (HMGB1), interleukin (IL)-33, S100 proteins, and heparan sulfate, into the intercellular space [22,49]. DAMPs are detected by immune cells with corresponding pattern recognition receptors (PRRs), such as the nucleotide-binding oligomerization domain, leucine-rich repeat-containing receptors (NLRs), and toll-like receptors (TLRs), which mediate the activation of intracellular pro-inflammatory signaling pathways [50,51].…”
Section: Inflammatory Responsementioning
confidence: 99%
“…Microglia, the resident central nervous system immune cells, are among the first cells to respond to these danger signals [50,52]. Within minutes of an injury, microglia are rapidly activated, undergo morphological changes, and secrete various cytokines [53,54].…”
Section: Inflammatory Responsementioning
confidence: 99%